Analysis of the Surface Subsidence of Porong and Surrounding Area, East Java, Indonesia based on Interferometric Satellite Aperture Radar (InSAR) Data. - Indra Arifianto; Rahmat Catur Wibowo (UIR PRESS, 2020)
Since 2006, the mud volcano erupted in the Porong area due to wellbore failure triggered by an earthquake (2006) epicenter in the Jogjakarta area. The mud volcano buried several villages with mud and continued erupted until today. Based on the InSAR data, it can be seen that the subsidence is still happening near the dam area and another area that is not related to mud volcano eruption such as the production of two gas fields in the Porong area. Moreover, the Porong area is flat and low, less than 4 meters above sea level. The analysis shows that the subsidence rate in this area is up to 0.5 m/yr. If this subsidence is continuing, the city can be sinking and flooding during the rainy season. The prediction result from this method is about 10 years more and 36 years since in 2006 based on the mudflow rate method.